From women to women—hematuria during therapy for metastatic breast cancer, what to suspect and when to be alarmed; Bladder metastasis from breast cancer—our experience and a systematic literature review - Malinaric, Rafaela; Balzarini, Federica; Granelli, Giorgia; Ferrari, Arianna; Trani, Giorgia; Ambrosini, Francesca; Mantica, Guglielmo; Panarello, Daniele; De Rose, Aldo Franco; Terrone, Carlo (Frontiers in Oncology, 2022)
Breast cancer is one of the most important causes of premature mortality in women worldwide. Around 12% of breast cancer patients will develop metastatic disease, a stage associated with poor prognosis, and only 26% of patients are likely to survive for at least 5 years after being diagnosed. Although the most common sites where breast cancer tends to spread are bones, lungs, brain, and liver, it is important that physicians consider other less frequent organs and viscera, like the bladder, as a target destination. In this article we report our experience with this rare form of metastases and a systematic literature review. We analyzed case reports, case series, and review articles present in PubMED/MEDLINE up to March 2022. We excluded the nonrelevant articles, editorials, letters to the editor, and articles written in other languages. We identified a total of 302 articles, with 200 articles being removed before screening; therefore, the total number of abstracts reviewed was 102. Fifty-five articles were excluded before full text review because they did not meet the inclusion criteria, and one article was not retrievable. Therefore, we included a total of 45 articles in this review. The intention of this review is to highlight the importance of the early detection of bladder metastases and to facilitate the diagnostic process for the responsible physician. The most common signs and symptoms and breast cancer subtype associated with bladder metastases, as well as overall survival after their detection, were all assessed. Bladder metastases from metastatic breast cancer are prevalent in the invasive, lobular breast cancer subtype; most patients present with hematuria (39.5%) and the relative 5-year survival rate is 2%. The main limitations of this review are the low number of cases reported in the literature, clinical and pathological differences between the individual cases, and absence of the control group. This study was not funded.